Communication and subjectivation in court settings: Approaches from forensic social work (Papeles, 2023)
State-judicial intervention is typically associated with the mere application of norms in legal conflicts. However, this operation involves mobilizing an institutional framework with significant subjective consequences. This institutionality is decisively supported by communication, which, depending on whether it takes instrumental forms or follows communicative rationality, will steer such subjectification in one direction or another. These effects are observed not only in the individuals subjected to the judicial process but also in the participants within the judicial apparatus. Therefore, it is just as pertinent to discuss forensic communication as it is to address the applicable legal norms, with particular attention to the naturalizations of various linguistic barriers and other elements that impede the aforementioned communication.
Keywords: Intervention; Forensic Social Work; Communication; Subjectivity; Sociolegal